Enhanced yeast feeding following mating facilitates control of the invasive fruit pest Drosophila suzukii. Issue 1 (26th May 2016) - Mori, Boyd A.; Whitener, Alix B.; Leinweber, Yannick; Revadi, Santosh; Beers, Elizabeth H.; Witzgall, Peter; Becher, Paul G.
Summary: The highly invasive spotted wing Drosophila Drosophila suzukii is a key pest of soft fruit and berries in Europe and North America, and development of control techniques is an urgent research challenge. Drosophila suzukii is widely associated with the yeast Hanseniaspora uvarum . Yeasts are symbionts of drosophilid flies and communicate with insects through volatile metabolites for spore dispersal. Accordingly, yeasts and behaviour‐modifying chemicals produced by yeasts are prospective tools for environmentally sound insect management. We first bioassayed flight attraction, feeding and oviposition of D. suzukii females in response to H. uvarum yeast and blueberries, which are a preferred host fruit. We then investigated the combined effect of yeast and insecticide on adult female oviposition behaviour and mortality towards the development of a yeast‐based control method. Following mating, attraction of female flies to blueberry and yeast odour cues was strongly enhanced. Yeast feeding significantly increased in mated females, while yeast did not increase oviposition on blueberries. This observation suggests that mated flies become attracted to yeast for feeding and to fruit for egg laying. A combined feeding–oviposition assay demonstrated different roles and interference between yeast and fruit stimuli: during the day after mating, females laid fewer eggs when yeast was available. The post‐mating yeast‐feeding response is an opportunity for the development of an attract‐and‐kill technique for population control of D. suzukii . Exposing flies to a blend of yeast and insecticide reduced oviposition and greatly enhanced adult fly mortality compared with an insecticide treatment alone. Synthesis and applications . Mated females are the key life stage for Drosophila suzukii population control. Egg‐laying females perforate fruit skin and fungal infestations ensue, even when eggs and larvae are killed off by insecticide sprays. Behaviour‐modifying chemicals, including yeast metabolites, enable environmentally safe insect management via manipulation of olfactory‐mediated reproductive behaviour. Our results highlight that yeast and yeast semiochemicals hold potential for D. suzukii management and that response modulation to olfactory stimuli following mating is a vital element for the development of D. suzukii control methods. Yeast feeding is enhanced in mated D. suzukii females, and this change in post‐mating behaviour can be exploited by an attract‐and‐kill strategy, combining a fly‐associated yeast with an insecticide. Furthermore, using the D. suzukii yeast mutualist, H. uvarum, may reduce non‐target effects and increase species specificity, which further contributes to the development of an efficient and safe control method.